PENGGUNAAN PENDEKATAN RESOURCE BASED LEARNING DALAM MENGANALISIS UNSUR CERITA ANAK SISWA KELAS V SD NEGERI 2 PULAU MOROTAI - M. Rais Salim (EDUKASI, 2016)
The aim of this research is to know the result of matter Annalysis cild story by using Resource Based Learning Approach after being implemented in language and arts learning.The kind of this research is Descriptive Quantitative. The subject of this research is the Fifth Class Students of Negeri 2 Pulau Morotai  which involves 10 students, the instrument of this research is observation and angket. Then, the students read matter of story child and answer the question based on personal experience. Date was analyzed by using descriptive analysis.The result of data analysis students matter of child story used Resource Based Learning approach was improved. There are 10 students who obtained very good (42,00%) the answer based on matter of child story, 10 students who obtained (28.00%) answered right based on matter of child story, and 10 students who answered (15.00%) based on matter of child story. Key words:  Resource Based Learning, Child Story Matter